Mejoramiento del proceso de producción de protectores de polietileno espumado mediante simulación dinámica - Ibarra, Mario (2009)
In the present work one gives an offer of improvement of the process of protectors' production of skimmed off polyethylene, also called by the producing company PIPES or simply profitable protectors, using the skill of dynamic simulation, realized in the software Witness. It started analyzing the current process, where by means of a field study, the sufficient information was obtained to realize the simulation of the above mentioned process. Then, by means of an analysis of the indicators thrown in the simulator, they gave to themselves 2 offers of improvement, where, after an exhaustive analysis to find the factors that would reverberate in the process if the respective changes were implemented, it was achieved to simulate the above mentioned offers and using the method Bonferroni, it was possible to choose the best. Finally an analysis did cost to itself benefit that would ensue from the implementation of the offer, comparing the states of results projected to 5 years of the current process vs the improved one, giving as result that the implementation of the proposed improvement is feasible.